GINGIVITIS: COURSE AND FEATURES - Dosmuxamedov Nodirbek Batirovich; Do'smuxamedova Shirina Nodirbek Qizi (Western European Studies, 2025)
Inflammatory gum diseases are common among people of different age groups, including more than half of children. Such diseases very often cause other dental and jaw diseases and loss of teeth. Therefore, it is simply necessary to identify and treat all diseases of the oral cavity, which can often go unnoticed. Gingivitis is one of the diseases of the dental and jaw system, which is characterized by inflammation of the mucous membrane of the gums. As for other tissues that are part of the gum, they remain intact during this disease. The ligamentous apparatus and bone tissue are not prone to changes. Basically, there is inflammation of the periodontium in the area of several teeth. The area of inflammation can vary depending on the age of the patient, consistency and quality of oral care, etc. The localization of this disease is basically the same - all areas that are poorly amenable to hygienic measures. Such areas include the interdental spaces of all chewing teeth. The risk group for this disease includes pregnant women, adolescents and people suffering from diabetes
Keywords: prone; diseases; Gingivitis